The handbook of conflict resolution : theory and practice - Coleman, Peter T., 1959-; Deutsch, Morton, 1920-; Marcus, Eric Colton (San Francisco, CA : Jossey-Bass, 2014)
'Written for both the seasoned professional and the student who wants to deepen their understanding of the processes involved in conflicts and their knowledge of how to manage them constructively, this book provides an understanding for managing conflicts at all levels--interpersonal, intergroup, organizational, and international. Each chapter focuses around a central case or illustration of the practice with a discussion for both training and direct intervention. This new edition includes companion downloadable chapters and new information on conflict resolution and IT, social networks, schools, families, environment and much more'--
Includes bibliographical references and index.
Keywords: Conflict management